CONTRADICTORY APPROACH TO PROJECT MANAGEMENT IN REGIONAL DEVELOPMENT IN BUKHARA (American Journal of Business Management, Economics and Banking, 2024)
This study explores the role of contradictions in project management within the regional development of Bukhara, focusing on the challenges posed by balancing modernization and cultural preservation. Through a multi-method approach, including case study analysis and stakeholder interviews, the research identifies the tensions between economic growth objectives and the protection of Bukhara’s rich cultural heritage. The findings reveal that while these contradictions create challenges, they also present opportunities for innovation in project management methodologies.Hybrid project management approaches, which combine Agile flexibility with traditional management structures, have proven effective in navigating the complex socio-economic landscape of Bukhara. The study highlights the importance of inclusive stakeholder engagement, where community involvement and iterative feedback were key to achieving both sustainable economic outcomes and cultural preservation goals.Contrary to viewing contradictions as obstacles, the research demonstrates that embracing these tensions can lead to creative solutions that respect both modern development needs and traditional values. The adaptive management strategies employed in successful projects in Bukhara offer insights for other regions facing similar development challenges.This study concludes that a contradictory approach to project management, which acknowledges and leverages inherent tensions, is crucial for achieving balanced, sustainable development in historically and culturally significant regions like Bukhara.